Littératie et résistances sociales face à l’implémentation du protocole de recherche numérique des « cas contacts des malades tuberculeux » en Côte d’Ivoire - Kouassi, Yao Cyrille; Irigo, Gbete Jean Martin; Angoa, Georgina; Koudou, Benjamin G. (European Scientific Journal, ESJ, 2026)
Depuis l’avènement du coronas virus 2019, les méthodes de recherche des cas contacts des malades contagieux ont été repensées. En effet, la forte contagiosité du COVID-19 a révélé les limites de la méthode manuelle et traditionnelle de la recherche et du suivi des cas contacts. Cette méthode, marquée essentiellement par des enquêtes épidémiologiques relativement longues s’avérait inadaptée face à des pathologies aussi rapidement contagieuses que le COVID-19. Par conséquent, la recherche et le suivi manuels ont progressivement été numérisés. Désormais, des dispositifs basés sur des smartphones ou en format capteurs enregistrent systématiquement les contacts des personnes qui utilisent ces plateformes. Toutefois, l’adhésion des usagers à l’innovation est confrontée à plusieurs formes de résistances sociales. Que ce soit dans les pays développés ou ceux en voie de l’être, le niveau d’adoption de la technologie est faible. En outre, ces plateformes sont pour la plupart conçues dans les pays développés et implémentés dans les autres, sans tenir compte des réalités sociales locales. Pourtant, l’acceptabilité sociale d’une technologie en e-santé prend ancrage dans l’appareil social et sur le niveau de littératie des usagers ciblés par le dispositif. Par conséquent, l’objectif de la présente étude est de déterminer la part de la littératie dans les résistances sociales liées à l’adoption d’une technologie de recherche et de suivi numérique des cas contacts des malades tuberculeux à Abobo (Côte d’Ivoire). The emergence of Coronavirus Disease 2019 (COVID-19) has profoundly transformed contact tracing strategies for infectious diseases. The rapid transmissibility of COVID-19 exposed the structural limitations of conventional manual contact tracing, which relies heavily on time-intensive epidemiological investigations and retrospective interviews. Such approaches proved insufficient in the face of highly contagious pathogens requiring rapid identification and interruption of transmission chains. In response, contact tracing practices were progressively digitized through the deployment of smartphone-based applications and wearable or sensor-based systems capable of automatically recording proximity events. Despite their epidemiological promise, digital contact tracing technologies have encountered persistent social resistance and limited adoption across both high-income and low- and middle-income countries. Adoption rates remain suboptimal, undermining the public health effectiveness of these tools. Furthermore, most digital tracing platforms are conceptualized and developed in technologically advanced contexts before being implemented elsewhere, often without adequate consideration of local socio-cultural, infrastructural, and literacy-related realities. The social acceptability of e-health technologies is not merely a function of technical performance but is deeply embedded in social structures, cultural norms, trust dynamics, and, critically, the level of health and digital literacy among target populations. Literacy shapes risk perception, technological comprehension, and the capacity to meaningfully engage with digital health innovations. Yet, its role in shaping resistance to digital contact tracing in sub-Saharan African contexts remains underexplored. This study therefore investigates the extent to which literacy contributes to social resistance to the adoption of a digital contact tracing and monitoring technology for tuberculosis in Abobo (Côte d’Ivoire). By situating technological adoption within its socio-cultural environment, this research aims to provide empirically grounded insights to inform the development of context-sensitive digital health interventions in low-resource settings.